Seismic Microzonation: A Case Study - Ansa, Atilla; Biro, Yeşim; Erken, Ayfer; Gülerce, Ümit (Kluwer Academic Publishers, 2006)
The major purpose of seismic microzonation is to offer urban planners and city officials some guidelines to mitigate earthquake risk. For this purpose, a seismic microzonation study was conducted for the Silivri Municipality in Istanbul. Assuming that the main factors affecting the earthquake characteristics on the ground surface are source and site factors, regional seismic hazard study was conducted at a regional scale adopting a single areal source model. The earthquake characteristics on the ground surface was determined based on the evaluation of site conditions with respect to equivalent shear wave velocity and with respect to site response analyses conducted for each representative soil profile. In determining the seismic microzonation for ground shaking, all available results were utilised by adopting a grid system to estimate the variation of spectral amplification in the investigated region, namely in the town of Silivri.